2019
DOI: 10.1111/all.13767
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of paediatric food allergy: A systematic review

Abstract: Background The genetic determinants of food allergy have not been systematically reviewed. We therefore systematically reviewed the literature on the genetic basis of food allergy, identifying areas for further investigation. Methods We searched three electronic databases (MEDLINE, EMBASE and PubMed) on 9 January 2018. Two authors screened retrieved articles for review according to inclusion criteria and extracted relevant information on study characteristics and measures of association. Eligible studies inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 73 publications
0
29
0
Order By: Relevance
“…Consequently, epithelial dysregulation and mutations or polymorphisms of genes important for skin barrier, such as filaggrin, SPINK5, 1 and SERPINB7, have been linked to eczema development and also food allergy. [2][3][4][5][6] Recently, electrical impedance spectroscopy has shown promising results in rodents to measure skin barrier function. This is of relevance since it can be easily adapted for usage on humans.…”
Section: Food Allergy and Barrier Functionmentioning
confidence: 99%
“…Consequently, epithelial dysregulation and mutations or polymorphisms of genes important for skin barrier, such as filaggrin, SPINK5, 1 and SERPINB7, have been linked to eczema development and also food allergy. [2][3][4][5][6] Recently, electrical impedance spectroscopy has shown promising results in rodents to measure skin barrier function. This is of relevance since it can be easily adapted for usage on humans.…”
Section: Food Allergy and Barrier Functionmentioning
confidence: 99%
“…In many of these studies, infants were sensitized just before introducing the allergenic food/s (4,24,26,27). This suggests that other factors, including genetics, epigenetics, and gut flora, could take part in FA development before weaning (52)(53)(54)(55)(56).…”
Section: Multiple Allergenic Foodsmentioning
confidence: 99%
“…Kurakula et al found that the SNP rs4851765 in FHL2 shows an association with the severity of bronchial hyper‐responsiveness, identifying FHL2 as a novel gene associated with asthma severity in humans. Furthermore, genome‐wide association studies (GWAS) were used to discover susceptibility genes for allergic diseases employing common SNPs, finding novel loci and confirmed the role of some previously described genes . Several loci have been found using GWASs in the last decade, such as HLA, MRPL4, BCAP, C11orf30/LRRC32, and FERD3L, which could be involved in inflammatory system or epithelial barrier functions .…”
Section: Risk Factorsmentioning
confidence: 93%
“…Furthermore, genome-wide association studies (GWAS) were used to discover susceptibility genes for allergic diseases employing common SNPs, finding novel loci and confirmed the role of some previously described genes. 16,17 Several loci have been found using GWASs in the last decade, such as HLA, MRPL4, BCAP, C11orf30/LRRC32, and FERD3L, which could be involved in inflammatory system or epithelial barrier functions. 18 Wagge et al 19 conducted a GWAS on sensitization to inhalant allergens, suggesting that AR and allergic sensitization might share biologic mechanisms and that allergic sensitization loci generally affect systemic allergic sensitization.…”
mentioning
confidence: 99%